OP0145 MALIGNANCY IN ANCA-ASSOCIATED VASCULITIS AND POLYARTERITIS NODOSA: AN AUSTRALIAN POPULATION-BASED STUDY. (2nd June 2020) - Tieu, J.; Lester, S.; Raymond, W.; Keen, H.; Hill, C.; Nossent, J.
Abstract : Background: The increased risk of malignancy in patients with ANCA-associated vasculitis (AAV) and polyarteritis nodosa (PAN) has been attributed to late treatment related effects, with non-melanoma skin and genitourinary cancers most frequently reported in European studies 1, 2, 3 . Malignancy has not been examined in patients with AAV/PAN in Australia, where environmental factors may influence risk. Objectives: To determine the risk and timing of incident cancer in Western Australian (WA) AAV/PAN patients compared to controls. Methods: Patients and controls were ascertained through the WA Hospital Morbidity Data collection System (HMDS). Administrative hospitalisation data were linked with the WA cancer and death registries. Data was available between 1980-2015. Patients were classified into two sub-groups using International Classification of Disease (ICD) -9 and/or -10 codes: (1) GPA/MPA- granulomatosis with polyangiitis (GPA)/microscopic polyangiitis (MPA), and (2) other-AAV/PAN- eosinophilic granulomatosis with polyangiitis (EGPA), PAN, and other patients with any AAV or PAN where more specific ICD-10 coding was not available. Controls were age, sex and temporally matched (at patient diagnosis date) and had no rheumatological diagnosis. Patients and controls with prior cancer were excluded from the analysis. Spline-based estimation of time-varying hazard ratios (HR) for incident cancer in patients vs controls was performed using the Stata library stpm2cr 4 . Results for cause-specific models, which treated deaths in patients without cancer as censored, were confirmed using models treating death as a competing risk. The risk of specific cancers was analysed by Cox regression. Results: The analysis included 391 patients (165 GPA/MPA, 217 other-AAV/PAN) and 4913 controls, with 86 incident cancers (over 3556.7 person-years) observed in patients and 1119 (over 64997.0 person-years) in controls. Patients and controls were well matched for age (mean ± standard deviation GPA/MPA: 55 ± 18 years, other AAV/PAN: 59 ± 17 years, controls 57 ± 16 years), and sex (female: GPA/MPA 48%, other AAV/PAN 46%, controls 46%). Incident cancer risk and timing differed between the two patient subgroups (Figure 1 ). The risk of incident cancer in GPA/MPA patients, compared to controls, increased with disease duration, whilst other-AAV/PAN patients had a greater risk within the first two years of diagnosis, but a similar risk to controls in the longer term. By specific cancers, GPA/MPA patients had an increased risk of skin cancers (excluding squamous and basal cell carcinomas): hazard radio (HR) 2.71 95% confidence interval (CI) 1.55 – 4.74, and genitourinary cancers: HR 3.64, 95% CI 1.58, 8.39, which was not observed in other-AAV/PAN patients. While there was trend for an overall increase in haematological cancers, this was inconclusive. Conclusion: Incident cancer risk, driven by skin and genitourinary cancers, increased with disease duration in GPA/MPA patients, consistent with previous studies, suggestive of a treatment related effect. In contrast, cancer was more frequently observed early after diagnosis in other-AAV/PAN patients. Our findings suggest that vigilance for incident cancers is required for all patients with AAV and PAN after diagnosis and in long term management, considering distinct periods of greater risk by disease subgroup. References: [1]Heijl C et al. Ann Rheum Dis 2011;70:1415-1421 [2]Lafarge A et al. Ann Rheum Dis 2019;0:1-2 [3]Farschou M et al. Rheumatology 2015;54:1345-1350 [4]Mozumder S et al. Stata J. 2017;17(2):462-489 Disclosure of Interests: Joanna Tieu: None declared, Susan Lester: None declared, Warren Raymond: None declared, Helen Keen Speakers bureau: Pfizer Austrlaia, Abbvie Australia, Catherine Hill: None declared, Johannes ("Hans") Nossent Speakers bureau: Janssen